Bioactive polymeric nanofiber matrices for skin regeneration. Issue 16 (8th January 2015) - Guadalupe, Eross; Ramos, Daisy; Shelke, Namdev B.; James, Roshan; Gibney, Christian; Kumbar, Sangamesh G.
ABSTRACT Electrospun nanofiber matrices have attracted a great deal of attention as matrices for skin repair and regeneration. The current manuscript reports the fabrication and characterization of a bioactive polycaprolactone (PCL) fiber matrix for its ability to deliver multiple factors. Bioactive PCL matrices were created by incorporating a model angiogenic factor and a model antibiotic drug. Chitosan coating on the fiber matrices significantly improved the ability to hold moisture and contributed to antibiotic activity. These fiber matrices have a modulus of 5.8 ± 1.3 MPa and matrices subjected to degradation over 4 weeks did not lose their tensile properties due to slow degradation rate. Chitosan coating avoided the initial burst release commonly associated with fiber matrices and only 60% of the encapsulated drug was released over a period of 15 days. Control PCL‐chitosan matrices were able to reduce Staphylococcus aureus (S. aureus) growth both in static and dynamic condition as compared to formulations with 50 mg gentamicin. In general, all the fiber matrices were able to support fibroblast growth and maintained normal cell morphology. Such bioactive bandages may serve as versatile and less expensive alternatives for the treatment of complex wounds. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41879.